2008
DOI: 10.1007/s00128-008-9472-z
|View full text |Cite
|
Sign up to set email alerts
|

Phytochelatins in the Diatom Phaeodactylum tricornutum Bohlin: An Evaluation of their Use as Biomarkers of Metal Exposure in Marine Waters

Abstract: The feasibility of a bioassay based on the synthesis of phytochelatins to assess metal pollution in aquatic environments was evaluated by using the marine diatom Phaeodactylum tricornutum. Short-term incubation experiments carried out in EDTA-buffered artificial seawater showed increasing cellular phytochelatin concentration with increasing free cadmium, lead or copper in the medium, indicating that phytochelatins behave as a biomarker of exposure to the bioavailable metal fraction. A linear dose-response rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Phytochelatins are synthesized from GSH, which is also known to respond to oxidative stress. However, while the intracellular abundance of PCs is thought to be linked to metal concentrations in the surrounding water (e.g., Ahner and Morel, 1995; Ahner et al, 1995; Morelli and Scarano, 2001; Dupont and Ahner, 2005; Le Faucheur et al, 2005; Kawakami et al, 2006b; Pawlik-Skowronska et al, 2007; Morelli and Fantozzi, 2008; Devez et al, 2009), cellular GSH abundance, and metal concentrations are not necessarily directly related (Kawakami et al, 2006c; Scheidegger et al, 2011). Glutathione has many metabolic roles (Mendoza-Cozatl et al, 2005), however, exogenous GSH is known to affect replication of Herpes simplex virus type 1 (HSV-1) by interfering with the very late stages of the virus life cycle, without otherwise affecting host cellular metabolism (Palamara et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochelatins are synthesized from GSH, which is also known to respond to oxidative stress. However, while the intracellular abundance of PCs is thought to be linked to metal concentrations in the surrounding water (e.g., Ahner and Morel, 1995; Ahner et al, 1995; Morelli and Scarano, 2001; Dupont and Ahner, 2005; Le Faucheur et al, 2005; Kawakami et al, 2006b; Pawlik-Skowronska et al, 2007; Morelli and Fantozzi, 2008; Devez et al, 2009), cellular GSH abundance, and metal concentrations are not necessarily directly related (Kawakami et al, 2006c; Scheidegger et al, 2011). Glutathione has many metabolic roles (Mendoza-Cozatl et al, 2005), however, exogenous GSH is known to affect replication of Herpes simplex virus type 1 (HSV-1) by interfering with the very late stages of the virus life cycle, without otherwise affecting host cellular metabolism (Palamara et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main strategies in algae for detoxification of metals involves generation of phytochelatins (PCs), which are synthesized from glutathione by phytochelatin synthase (PCS). 37 A recent analysis of PC production in P. tricornutum showed that cadmium induces PC production at Cd 2+ concentrations down to 0.2 nM, 38 and PC levels increase rapidly upon Cd exposure in Thalassiosira nordenskioeldii. 39 Transcription of PCS is not induced by Cd exposures in our study.…”
Section: ' Discussionmentioning
confidence: 99%
“…Marine and freshwater diatoms are also widely used in monospecific bioassays to study the effects of liquid and solid chemical substances and generate toxicity data as part of risk assessment and monitoring programs (Blaise and Me ´nard 1998;Blaise and Vasseur 2005;Arau ´jo et al 2010). Diatom bioassays have also been used to assess concentrations of phytochelatins in order to appraise the bioavailability of metals/metalloids in water and sediment (Morelli and Fantozzi 2008;Morelli et al 2009).…”
Section: Applications In Ecotoxicologymentioning
confidence: 99%